Tìm x:
a) 0 . 5x = 0; b) 3( x - 2) = 0.
Tìm x:
a)(5x-1)(5x+1)=15
b)x2-8x+16-(5x+2)2=0
c)x2-10x+9=0
\(a,25x^2-1=15\)\(< =>x^2=\dfrac{16}{25}< =>x=\pm\dfrac{4}{5}\)
\(b,\left(x-4\right)^2-\left(5x+2\right)^2=0\)\(< =>\left(-4x-6\right)\left(6x-2\right)=0\)
\(< =>\left[{}\begin{matrix}x=-\dfrac{3}{2}\\x=\dfrac{1}{3}\end{matrix}\right.\)
\(c,\left(x-1\right)\left(x-9\right)=0< =>\left[{}\begin{matrix}x=1\\x=9\end{matrix}\right.\)
Tìm x:
a)2.(x+5)-x2-5x=0
b)6x2-7x+2=0
a.
\(2\left(x+5\right)-x^2-5x=0\)
\(\Leftrightarrow2\left(x+5\right)-x\left(x+5\right)=0\)
\(\Leftrightarrow\left(2-x\right)\left(x+5\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}2-x=0\\x+5=0\end{matrix}\right.\) \(\Rightarrow\left[{}\begin{matrix}x=2\\x=-5\end{matrix}\right.\)
b.
\(6x^2-7x+2=0\)
\(\Leftrightarrow6x^2-3x-4x+2=0\)
\(\Leftrightarrow3x\left(2x-1\right)-2\left(2x-1\right)=0\)
\(\Leftrightarrow\left(3x-2\right)\left(2x-1\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x=\dfrac{2}{3}\\x=\dfrac{1}{2}\end{matrix}\right.\)
Tìm x:
a)x2-4x=3.(x-4)
b)x2-5x-24=0
a: \(x^2-4x=3\left(x-4\right)\)
\(\Leftrightarrow\left(x-4\right)\left(x-3\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x=4\\x=3\end{matrix}\right.\)
b: \(x^2-5x-24=0\)
\(\Leftrightarrow\left(x-8\right)\left(x+3\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x=8\\x=-3\end{matrix}\right.\)
a) pt <=> (x - 4)(x - 3) = 0
<=> x = 4 hoặc x = 3
b) pt <=> (x - 8)(x + 3) = 0
<=> x = 8 hoặc x = -3
tìm x:
a)\(\dfrac{-3}{x+5}< 0\) b)\(\dfrac{2x+1}{7}< 0\) c)x\(^2\) - 5x + 4 >0 d)\(\dfrac{x+1}{x-1}< 1\)
a) 1\(\dfrac{2}{3}\). b)\(\dfrac{1}{7}\). c) 1 d )0
a: =>x+5>0
hay x>-5
b: =>2x+1<0
hay x<-1/2
c: =>(x-1)(x-4)>0
=>x>4 hoặc x<1
a) x>-5 ĐKXĐ x\(\ne\)-5
b)x<\(-\dfrac{1}{2}\)
c)x>4 hoặc x<1
d)ĐKXĐ x\(\ne\)1, ko tìm đc x
Tìm x:
a) 5x+40x4=0
b) 8x2-2x-1=0
c) (3x2+x)2-(3x2+x)-2=0
a: Ta có: \(40x^4+5x=0\)
\(\Leftrightarrow5x\left(8x^3+1\right)=0\)
\(\Leftrightarrow x\left(2x+1\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x=0\\x=-\dfrac{1}{2}\end{matrix}\right.\)
b: Ta có: \(8x^2-2x-1=0\)
\(\Leftrightarrow8x^2-4x+2x-1=0\)
\(\Leftrightarrow\left(2x-1\right)\left(4x+1\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x=\dfrac{1}{2}\\x=-\dfrac{1}{4}\end{matrix}\right.\)
Tìm x:
a) (x-2)2-(x2-3x)=9
b) (5x-2)2=(4-x)2
c) x2-4x-5=0
a) \(\left(x-2\right)^2-\left(x^2-3x\right)=9\)
\(\Rightarrow x^2-4x+4-x^2+3x-9=0\)
\(\Rightarrow-x-5=0\)
=> x = -5
b) \(\left(5x-2\right)^2=\left(4-x\right)^2\)
\(\Rightarrow25x^2-10x+4-16+8x-x^2=0\)
\(\Rightarrow24x^2-2x-12=0\)
\(\Rightarrow12x^2-x-6=0\)
\(\Rightarrow\left[{}\begin{matrix}x=-\dfrac{2}{3}\\x=\dfrac{3}{4}\end{matrix}\right.\)
c) \(x^2-4x-5=0\)
=> (x - 5).(x + 1) = 0
=> x = 5 hoặc x = -1
a)\(\left(x-2\right)^2-\left(x^2-3x\right)=9\)
\(x^2-4x+4-x^2+3x=9\)
\(-x+4=9\)
\(-x=5\)
\(x=-5\)
Tìm x:
a) (x-2)2-(x2-3x)=9
b) (5x-2)2=(4-x)2
c) x2-4x-5=0
a) \(\left(x-2\right)^2-\left(x^2-3x\right)=9\)
\(x^2-4x+4-x^2+3x=9\)
\(-x+4=9\)
-x=5
x=-5
\(\left(5x-2\right)^2=\left(4-x\right)^2\)
⇒5x-2=4-x⇒6(x-1)=0⇒x=1
hoặc -5x+2=-4+x⇒-6(x+1)=0⇒x=-1
c)\(x^2-4x-5=0\)
\(\left(x^2-4x+4\right)-9=0\)
\(\left(x-2\right)^2=9\)
⇒TH1:x-2=3⇒x=5
TH2:x-2=-3⇒x=-1
Tìm X:
a) 16x2-24x+9=25
b) x2+10x+9=0
c) x2-4x-12=0
d) x2-5x-6=0
e) 4x2-3x-1=0
f) x4+4x2-5=0
`a)16x^2-24x+9=25`
`<=>(4x-3)^2=25`
`+)4x-3=5`
`<=>4x=8<=>x=2`
`+)4x-3=-5`
`<=>4x=-2`
`<=>x=-1/2`
`b)x^2+10x+9=0`
`<=>x^2+x+9x+9=0`
`<=>x(x+1)+9(x+1)=0`
`<=>(x+1)(x+9)=0`
`<=>` \(\left[ \begin{array}{l}x=-9\\x=-1\end{array} \right.\)
`c)x^2-4x-12=0`
`<=>x^2+2x-6x-12=0`
`<=>x(x+2)-6(x+2)=0`
`<=>(x+2)(x-6)=0`
`<=>` \(\left[ \begin{array}{l}x=-2\\x=6\end{array} \right.\)
`d)x^2-5x-6=0`
`<=>x^2+x-6x-6=0`
`<=>x(x+1)-6(x+1)=0`
`<=>(x+1)(x-6)=0`
`<=>` \(\left[ \begin{array}{l}x=6\\x=-1\end{array} \right.\)
`e)4x^2-3x-1=0`
`<=>4x^2-4x+x-1=0`
`<=>4x(x-1)+(x-1)=0`
`<=>` \(\left[ \begin{array}{l}x=1\\x=-\dfrac14\end{array} \right.\)
`f)x^4+4x^2-5=0`
`<=>x^4-x^2+5x^2-5=0`
`<=>x^2(x^2-1)+5(x^2-1)=0`
`<=>(x^2-1)(x^2+5)=0`
Vì `x^2+5>=5>0`
`=>x^2-1=0<=>x^2=1`
`<=>` \(\left[ \begin{array}{l}x=1\\x=-1\end{array} \right.\)
Tìm x:
a)5x(x-2)-2x+4=0
b)2x(x+1)-(x-2)^2=6
c)2x^2+7x-9=0
\(a,\Leftrightarrow\left(x-2\right)\left(5x-2\right)=0\Leftrightarrow\left[{}\begin{matrix}x=2\\x=\dfrac{2}{5}\end{matrix}\right.\\ b,\Leftrightarrow2x^2+2x-x^2+4x-4-6=0\\ \Leftrightarrow x^2+6x-10=0\\ \Leftrightarrow\left[{}\begin{matrix}x=-3+\sqrt{19}\\x=-3-\sqrt{19}\end{matrix}\right.\\ c,\Leftrightarrow2x^2-2x+9x-9=0\\ \Leftrightarrow\left(2x+9\right)\left(x-1\right)=0\Leftrightarrow\left[{}\begin{matrix}x=-\dfrac{9}{2}\\x=1\end{matrix}\right.\)
Tìm x:
a)(x-6)2-(x+6)2=12
b)36x2-12x+1=81
c)x2-4x-12=0
d)x2-5x-6=0
`a)(x-6)^2-(x+6)^2=12`
`<=>(x-6-x-6)(x-6+x+6)=12`
`<=>-12.2x=12`
`<=>2x=-1`
`<=>x=-1/2`
Vậy `x=-1/2`
`b)36x^2-12x+1=81`
`<=>(6x-1)^2=81`
`<=>(6x-1-9)(6x-1+9)=0`
`<=>(6x-10)(6x+8)=0`
`<=>(3x-5)(3x+4)=0`
`<=>` \(\left[ \begin{array}{l}x=\dfrac53\\x=-\dfrac43\end{array} \right.\)
`c)x^2-4x-12=0`
`<=>x^2-6x+2x-12=0`
`<=>x(x-6)+2(x-6)=0`
`<=>(x-6)(x+2)=0`
`<=>` \(\left[ \begin{array}{l}x=-2\\x=6\end{array} \right.\)
`d)x^2-5x-6=0`
`<=>x^2-6x+x-6=0`
`<=>x(x-6)+x-6=0`
`<=>(x-6)(x+1)=0`
`<=>` \(\left[ \begin{array}{l}x=6\\x=-1\end{array} \right.\)